Principles of electronic materials and devices - Kasap, S. O. (McGraw - Hill, 2006)
This book is a greatly enhanced version of the highly successful text Principles of Electronic Materials and Devices, Second Edition. It is designed for a first course on electronic materials given in Materials Science and Engineering, Electrical Engineering, and Physics and Engineering Physics Departments at the undergraduate level.